Pengaruh Penerapan Pengendalian Biaya Kualitas Terhadap Peningkatan Produktivitas Di PT Pertamina Internasional Shipping(PIS) - Berliana Eka; Reinold Alvino; Venski Revalina; Henny Rakhmawati (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study aims to analyze the effect of implementing quality cost control on productivity improvement at PT Pertamina Internasional Shipping. Quality costs consist of four main components: prevention costs, appraisal costs, internal failure costs, and external failure costs. In the context of the energy industry, such as PIS, quality cost control is crucial to ensure operational efficiency and enhance productivity. The research method used is a quantitative approach based on secondary data obtained from the company's annual report for the year 2023. The analysis was carried out by identifying trends in quality costs and productivity, as well as the relationship between the two. The results show a positive and significant impact of quality cost control on work productivity. With optimal implementation of quality cost control, PIS is able to minimize losses due to product defects and improve efficiency in the production process. This study recommends that the company continue to enhance its quality control system as a strategy for long-term performance improvement.